Kualitas Pelayanan dan Akuntabilitas Pegawai dalam Meningkatkan Kepuasan Publik: Analisis PLS-SEM dengan Perspektif Islam pada Perumda Air Minum Lae Nciho, 2025 - Enia Fadila Sitakar; Imsar; Nurbaiti (Jurnal Ilmiah Mahasiswa Raushan Fikr, 2025)
This study examines how operational performance, service quality, and accountability influence public satisfaction at Perumda Air Minum Lae Nciho within an Islamic framework. Motivated by recurring complaints of unequal distribution, poor service, and delayed responses, the research underscores public service as an amanah requiring ihsan, in line with the Prophet’s teaching on itqan. Using a quantitative design with purposive sampling, 102 customers were surveyed and data analyzed through SEM-PLS. The model showed strong fit (SRMR = 0.062; Q2 > 0), with operational performance having the greatest effect (beta = 0.573), followed by service quality (beta = 0.240) and accountability (beta = 0.187). The model explained 86.4% of satisfaction variance (R2 = 0.864). Findings highlight the role of amanah, responsibility, and maqasid al-shariah in improving service quality. Recommendations include structured distribution, an online complaint system, and employee capacity building. Limitations relate to regional focus and variable scope; future studies should integrate technological innovation and Islamic leadership.